Climate change and occupational heat stress: methods for assessment - Ingvar Holmér (Taylor & Francis Group, 2010)
Background: Presumed effects of global warming on occupational heat stress aggravate conditions in many parts of the world, in particular in developing countries. In order to assess and evaluate conditions, heat stress must be described and measured correctly. Objective: Assessment of heat stress using internationally recognized methods. Design: Two such methods are wet bulb globe temperature (WBGT; ISO 7243) and predicted heat strain (PHS; ISO 7933). Both methods measure relevant climatic factors and provide recommendations for limit values in terms of time when heat stress becomes imminent. The WBGT as a heat stress index is empirical and widely recognized. It requires, however, special sensors for the climatic factors that can introduce significant measurement errors if prescriptions in ISO 7243 are not followed. The PHS (ISO 7933) is based on climatic factors that can easily be measured with traditional instruments. It evaluates the conditions for heat balance in a more rational way and it applies equally to all combinations of climates. Results: Analyzing similar climatic conditions with WBGT and PHS indicates that WBGT provides a more conservative assessment philosophy that allows much shorter working time than predicted with PHS. Conclusions: PHS prediction of physiological strain appears to fit better with published data from warm countries. Both methods should be used and validated more extensively worldwide in order to give reliable and accurate information about the actual heat stress.